QUALITY OF WORKLIFE BALANCE A STUDY IN GOOD LEAPS SOLUTIONS PRIVATE LIMITED (International Journal of Food and Nutritional Sciences, 2022)
The study conducted on the research topic “A Study on Work Life Balance of Employees of Good Leaps Solutions Private Limited. Work life balance is an important aspect of a healthy work environment. Maintaining work-life balance helps reduce stress and helps reduce stress and helps prevent burnout in the workplace. By creating a work environment that prioritizes work life balances, employees can save money and maintain a healthier, more productive work force. Work-life balance is about effectively managing the juggling act between paid work and the other activities that are important to people. It's not about saying that work is wrongor bad, but that work shouldn't completely crowd out the other things that matter to people like time with family, participation in community activities, voluntary work, personal development, leisure and recreation.